STRATEGI GURU DALAM MEMBANGUN KERJASAMA DENGAN ORANG TUA DALAM PENDIDIKAN ANAK USIA DINI DI TK KRISTEN RAJAWALI SAKTI-3 - Ayut Nursusanti; Wirastiani Binti Yusup; Della Gita Van Gobel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze teachers' strategies in building cooperation with parents in early childhood education at Rajawali Sakti-3 Christian Kindergarten, as well as to identify the obstacles faced by teachers in establishing such cooperation. This research employs a qualitative approach with a descriptive qualitative method. Data were collected through observation, in-depth interviews, and documentation. The informants consisted of the school principal, three class teachers (Class A, B1, and B2), and three parents. The findings reveal that teachers successfully established good cooperation with parents through active two-way communication and the use of digital media, such as WhatsApp groups, communication books, and digital folders for documenting children's development. This strategy aims to align education at school and at home. The challenges faced by teachers include time constraints and parents' busy schedules, differing perspectives between parents' expectations and the school's curriculum, lack of initiative from some parents in continuing character habituation at home, barriers to digital communication, and inconsistencies in supporting children at home. Effective cooperation between teachers and parents through intensive and ongoing communication can support children's character development, independence, and readiness to move on to the next level of education.